PRÁCTICAS INCLUSIVAS Y SU IMPLICACIÓN EN LA FORMACIÓN INTEGRAL DE LOS ESTUDIANTES DE NOVENO AÑO DE EGB DE LA U.E. FRANCISCO HUERTA RENDÓN, BABAHOYO-LOS RÍOS, 2024. - MORAN CANTOS, JORDAN STALIN (2024)
The objective of this curricular integration work was to determine how inclusive practices are involved in the overall training of students. The methodology used was the quantitative and qualitative approach, a type of descriptive, explanatory and documentary research, with a non-experimental design. The population was made up of 1,759 students at the institutional level and the sample that was carried out was of census type, which made it possible to cover the total of 25 students who make up the ninth year of the parallel EGB “C”. The technique was the survey which used as instrument a questionnaire composed of 14 questions with the structure of the Likert scale. The context and theoretical bases used in the associated classrooms were presented, and it was also possible to identify the lack of teacher training in carrying out the teaching process. For this reason, it was suggested that teacher preparation processes be carried out to effectively respond to the needs of students, since these educational actions allow educational quality to be achieved through the active participation of those who make up the educational centers.